Professional support during the postpartum period: primiparous mothers' views on professional services and their expectations, and barriers to utilizing professional help - Yiping Nan; Jingjun Zhang; Anum Nisar; Lanting Huo; Lei Yang; Juan Yin; Duolao Wang; Atif Rahman; Yan Gao; Xiaomei Li (BMC, 2020)
Abstract Background Primiparous mothers who lack of experience and knowledge of child caring, are usually overwhelmed by multifarious stressors and challenges. Although professional support is needed for primiparas, there is a gap between the necessary high-quality services and the currently provided poor services. This study aimed to explore Chinese primiparous mothers' views on professional services, identify barriers to utilizing professional support, and further understand mothers' expectations of and preferences for the delivery of professional services. Method A descriptive phenomenological study design was utilized in this study, and semi-structured interviews were conducted with 28 primiparous mothers who had given birth in the first year period before the interview and were selected from two community health centres in Xi'an city, Shaanxi Province, Northwest China. Each conversational interview lasted between 20 and 86 min. Colaizzi's seven-step phenomenological approach was used to analyse the data. Results Three major themes were identified: (a) dissatisfaction with current professional services for postpartum mothers, (b) likelihood of health care professional help-seeking behaviour, (c) highlighting the demands for new health care services. The related seven sub-themes included being disappointed with current hospital services; distrusting services provided by community health centres, private institutes and commercial online platforms; preferring not seeking help from professionals as their first choice; hesitating to express their inner discourse to professionals; following confinement requirement and family burden prevents mothers from seeking professional help; experiencing urgent needs for new baby-care-related services; and determining the importance of mothers' needs. The necessity of professional support in the first month after childbirth was strongly emphasized by the participants. Online professional guidance and support were perceived as the best way to receive services in this study. Conclusion The results of this descriptive phenomenological study suggested that the current maternal and child health care services were insufficient and could not meet primiparous mothers' need. The results also indicated that identifying barriers and providing services focused on mothers' needs may be an effective strategy to enhance primiparous mothers' well-being, and further suggested that feasibility, convenience, and the cultural adaptability of health care services should be considered during the delivery of postpartum interventions.